Comparison of the corrosion resistance of DIN W. Nr. 1.4970 (15%Cr-15%Ni-1.2%Mo-Ti) and ASTM F-138 (17%Cr-13%Ni-2.5%Mo) austenitic stainless steels for biomedical applications - Terada,Maysa (2006)
The resistance to localised corrosion of the full austenitic 15%Cr-15%Ni-1.2%Mo titanium stabilized stainless steel (DIN W. Nr. 1.4970) was investigated by electrochemical methods including electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and potentiostatic polarization measurements in a phosphate-buffered solution (PBS). The low carbon and non-stabilized austenitic stainless steel, AISI 316L (ASTM F-138), widely used for surgical implants, was also tested for comparison. The tests were conducted at room temperature after a stable potential had been reached. After the electrochemical measurements, the surfaces of the specimens were observed using SEM to evaluate the presence of pits. Potentiodynamic polarization results showed that both steels are prone to localized corrosion. Larger pits were found on the surface of AISI 316L specimens after the electrochemical tests. EIS response has indicated the duplex structure of the passive oxides. The results showed that the electrochemical behaviour of the DIN W. Nr. 1.4970 is better than of AISI 316L steel. Therefore, their application as an implant material may be considered.